DEVELOPMENT OF RP-HPLC METHOD FOR QUALITATIVE ANALYSIS OF ACTIVE INGREDIENT (GALLIC ACID) FROM STEM BARK OF DENDROPHTHOE FALCATE LINN. (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
A simple, precise and sensitive, RP-HPLC method with UV detection at 271nm was developed and validated for qualitative determination of active ingredient Gallic acid from stem bark of Dendrophthoe falcate Linn. Separation was performed on a ThermoMOS 2 HYPERSIL C18 column (250 cm × 4.6 mm, 5µm ODS 3) using mobile phase comprising of 0.1% Orthophosphoric acid : Acetonitrile (400 cm3 : 600 cm3) with a flow rate of 1 ml/minute with a short run time of 13 minute. The method was validated according to the regulatory guidelines with respect to linearity, system suitability, precision, solution stability, accuracy, robustness, assay and recovery. Detector response was linear for HPLC in the range of 0.04 to 0.16 mg/cm3. The system suitability, precision, solution stability, accuracy, robustness, assay and recovery was assessed by calculating % COV for all these parameters which is less than two as expected. The recovery of the method for Gallic acid was found 98.94% which shows that method is accurate. The described method has the advantage of being rapid and easy hence it can be applied for routine quality control analysis of Gallic acid from Dendrophthoe falcate Linn.